Clinical profile, prognosis and post COVID-19 Illnesses among attendants to private general practitioner (GP) clinic at Urban Amman Area: a clinical case-series study - Abuzayed, Esraa; Abuzayed, Ishtaiwi (Journal of Community Medicine and Health Solutions, 2023)
Background: The clinical manifestations of Corona Virus Disease of 2019 (COVID-19) varied from patient to patient with evidence of multi-organ involvement. Many patients continue to have a wide range of symptoms for variable periods of time. The long-term effects of COVID-19 infection (post-COVID-19 illness or syndrome) are not yet been fully explored. This study aims to highlight the clinical manifestations of the acute COVID-19 infection and the longer-term manifestations of the disease among the attendants to a private GP clinic in the Urban Amman Area, Jordan. Methods: A clinical case-series study was conducted on a sample of 300 COVID-19-positive cases among patients attending my private GP clinic in the Urban Amman Area, Jordan. We used the structured questionnaire based mainly on World Health Organization (WHO) Case Report Form (CRF) verified tool for post-COVID-19. All patients with COVID-19 were included in the study. Data collection was conducted through phone calls and analyzed using the Statistical Package for Social Sciences (SPSS) software. Results: The incidence of COVID-19 among patients attending the clinic during the period of this study was 25%. Females were 135 (45%) of the study population and males were 165 (55%). The mean (SD) of age was 34.2 (5.0) years. Most of the infected staff (90%) were symptomatic and developed acute COVID-19 symptoms. Fever, Cough, Fatigue, joint pain and loss of smell and taste were the most common symptoms. 72% of the study population had fully recovered from the infection, while 28% of them continued to suffer from many long symptoms. Fatigue (28%), shortness of breath on activity (18%), Social withdrawal (18%), anxiety (17%), forgetfulness (16%), trouble concentrating (15) and depressed mood (14%) were the most frequently reported long symptoms. Conclusion: The prevalence of Post COVID-19 illness was 28% with a high public health burden calling for the public health system to address the medical and psychological needs of affected persons. Mental health and psychosocial support are recommended elements for the management of patients.